Case Study: Green Event Through the Use of Renewable Energy in Organizing the Get the Fest 2022 Event - HENDRATMO, Cestia Astutiningsih; LEMY, Diena Mutiara; KUSUMO, H.K. Elang (PT Keberlanjutan Strategis Indonesia, 2024)
Events as a catalyst for the revival of tourism after the pandemic are the focus issues in event development in Indonesia. Events are one of the typical tourism activities with a